The conjugate-gradient nonuniform fast Fourier transform (CG-NUFFT) method for one- and two-dimensional media - Xu, Xue Min; Liu, Qing Huo (Microwave and optical technology letters, 2000)
A novel method combining the conjugate‐gradient and nonuniform fast Fourier transform (CG–NUFFT) algorithms for solving integral equations in electromagnetics is presented. The CG–NUFFT method has been applied to one‐ and two‐dimensional inhomogeneous media. Numerical results show the advantages of the CG–NUFFT method over the CG–FFT method for problems with both electrically large and small regions. © 2000 John Wiley & Sons, Inc. Microwave Opt Technol Lett 24: 385–389, 2000.